THE RELATIONSHIP OF EDUCATION BY ANIMATED VIDEOS AND LEAFLETS WITH MOTHERS’ KNOWLEDGE ABOUT ANEMIA IN PREGNANT WOMEN - Thyrister Nina Asarya Sembiring; Erick Darossi Sinulingga; Gloria Lumingkewas; Grace Dwie Saputri; Luther Gideon Eric Maruli Parhusip; Theresa Oktoberia; Dalia Ranti; Frendy Setiawan (Universitas Kusuma Husada Surakarta, 2026)
Background: Anemia in pregnant women remains a significant public health issue in Indonesia, including in the working area of the UPTD Kereng Bangkirai Community Health Center in Palangka Raya City. Based on data from 2023 and 2024, there has been an increase in cases of anemia in pregnant women from 5 cases to 25 cases. This study aims to determine the relationship between pregnant women's knowledge level and the incidence of anemia, and to evaluate the effectiveness of health education in improving their knowledge and awareness.Methods: The method used is a pre-experimental approach. The design used was a one-group pretest-posttest design with a sample consisting of 77 pregnant women at the UPTD Kereng Bangkirai Community Health Center in Palangka Raya City, selected using purposive sampling based on inclusion criteria. Education was provided through animated videos and leaflets, accompanied by pretest and posttest questionnaires.Results: The results showed a significant increase in knowledge after the education intervention (p=0.000). The results of this study indicate that education by animated videos and leaflets is effective in increasing mothers' knowledge about anemia during pregnancy.Conclusion: There is a relationship between education by animated videos and leaflets and mothers' knowledge about anemia in pregnant women. This is important in maternal health services at community health centers to reduce the rate of anemia and improve the quality of maternal health during pregnancy.